Performance of the FilmArray® blood culture identification panel utilized by non‐expert staff compared with conventional microbial identification and antimicrobial resistance gene detection from positive blood cultures. Issue 7 (July 2016) - McCoy, Morgan H.; Relich, Ryan F.; Davis, Thomas E.; Schmitt, Bryan H.
Abstract : N/A: Utilization of commercially available rapid platforms for microbial identification from positive blood cultures is useful during periods of, or in laboratories with, limited expert staffing. We compared the results of the FilmArray ® BCID Panel performed by non‐expert technologists to those of conventional methods for organism identification performed by skilled microbiologists. Within 8 h of signalling positive by a continuous monitoring blood culture system, positive bottles were analysed by the FilmArray BCID Panel. Data from these analyses were compared to standard‐of‐care testing, which included conventional and automated methods. To gauge the ease of use of the BCID Panel by non‐expert staff, technologists unfamiliar with diagnostic bacteriology performed the testing without prior knowledge of the Gram stain results, or even whether organisms were detected. Identifications of 172/200 (86 %) positive blood cultures using the BCID Panel were consistent with identifications provided by standard‐of‐care methods. Standard‐of‐care testing identified organisms in 20 positive blood cultures, which were not represented on the BCID Panel. Seven (3.5 %) blood cultures demonstrated a discrepancy between the methods, which could not be attributed to either a lack of representation on the panel or unclear separate detection of organisms in a mixed blood culture of a shared genus or grouping of organisms, e.g. Staphylococcus or Enterobacteriaceae . One (0.5 %) blood culture yielded invalid results on two separate panels, so it was eliminated from the study. The easy‐to‐use FilmArray ® technology shows good correlation with blood culture identification and antibiotic resistance detection performed by conventional methods. This technology may be particularly useful in laboratories with limited staffing or limited technical expertise.